Therapeutic Potential of Vital Transcription Factors in Alzheimer’s and Parkinson’s Disease With Particular Emphasis on Transcription Factor EB Mediated Autophagy - Rai, Sachchida Nand; Tiwari, Neeraj; Singh, Payal; Mishra, Divya; Singh, Anurag Kumar; Hooshmandi, Etrat; Vamanu, Emanuel; Singh, Mohan P. (Frontiers in Neuroscience, 2021)
Autophagy is an important cellular self-digestion and recycling pathway that helps in maintaining cellular homeostasis. Dysregulation at various steps of the autophagic and endolysosomal pathway has been reported in several neurodegenerative disorders such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and Huntington disease (HD) and is cited as a critically important feature for central nervous system (CNS) proteostasis. Recently, another molecular target, namely transcription factor EB (TFEB) has been explored globally to treat neurodegenerative disorders. This TFEB, is a key regulator of autophagy and lysosomal biogenesis pathway. Multiple research studies suggested therapeutic potential by targeting TFEB to treat human diseases involving autophagy-lysosomal dysfunction, especially neurodegenerative disorders. A common observation involving all neurodegenerative disorders is their poor efficacy in clearing and recycle toxic aggregated proteins and damaged cellular organelles due to impairment in the autophagy pathway. This dysfunction in autophagy characterized by the accumulation of toxic protein aggregates leads to a progressive loss in structural integrity/functionality of neurons and may even result in neuronal death. In recent years TFEB, a key regulator of autophagy and lysosomal biogenesis, has received considerable attention. It has emerged as a potential therapeutic target in numerous neurodegenerative disorders like AD and PD. In various neurobiology studies involving animal models, TFEB has been found to ameliorate neurotoxicity and rescue neurodegeneration. Since TFEB is a master transcriptional regulator of autophagy and lysosomal biogenesis pathway and plays a crucial role in defining autophagy activation. Studies have been done to understand the mechanisms for TFEB dysfunction, which may yield insights into how TFEB might be targeted and used for the therapeutic strategy to develop a treatment process with extensive application to neurodegenerative disorders. In this review, we explore the role of different transcription factor-based targeted therapy by some natural compounds for AD and PD with special emphasis on TFEB.